Analisis Deformasi Lateral dan Getaran Tanah Akibat Pemancangan Tiang pada Pipa Minyak dan Gas - Arraya Fredericko Romanza; Yerry Kahaditu Firmansyah; Dian Purnamawati Solin (AGREGAT, 2026)
The reclamation project of Triangle Island within the Java Integrated Industrial Port Estate (JIIPE) necessitates the installation of driven deep foundations in soft clay deposits adjacent to existing oil and gas pipelines. The pile driving process induces lateral soil deformation and ground vibration, posing a severe threat to pipeline integrity. This study evaluates the geotechnical impacts of pile driving and proposes effective mitigation measures. The structural viability of the foundation was initially validated using the Nakazawa method with corrected parameters for bearing capacity, alongside immediate settlement analysis using the Bowles equivalent raft approach for a 37-meter deep, 600 mm diameter steel pipe pile group. Subsequently, two-dimensional numerical modeling using finite element methods was conducted to simulate lateral soil displacement and ground vibration generated by a Junttan HHK 7A hydraulic impact hammer. Several mitigation scenarios, primarily focusing on pre-boring configurations, were analyzed. The unmitigated numerical results demonstrate that stress and lateral displacement around the pipeline approach or exceed allowable design limits. However, the implementation of optimized pre-boring significantly attenuates soil heave and vibration response, keeping pipeline deformations within safe operational thresholds. These findings provide a robust